PENGARUH PERSEPSI HARGA DAN DESAIN TERHADAP KEPUTUSAN PEMBELIAN PENGGUNA MOTOR KLX KAWASAKI DI SURABAYA TIMUR - Herdian, Panji Dwi; Maruta, IGN Anom; Mulyati, Diana Juni (Jurnal Dinamika Administrasi Bisnis, 2018)
Each motorcycle manufacturer must have their own strategy in running their business both in terms of price, design and so forth in order to sell all products that interested so that consumers nwill be interested and then decide the ourchase. This study aims to determine the influence of price perception and desaign on purchasing decision Kawasaki motorcycle, Kawasaki is a famous motorcycle brand and is known as a sporty and modern motorcycle product for the current millennial generation.The number of motorcycle user population is not known for certain, taking sample number is detrmined as 96 respondents by using method of convenience sampling and with determination never use the motor. The data collected by spreading questioner filled by user then analyxed by using multiple regression analysis. The analysis includes Validity test, Reliability test, Multicollinearity test, Normality test, Heteroskedasticity test, Autucorrelation test, Determination test (R), Correlation test, Multiple Linear Regression Analysis (F)), Partial test (t).Result research shows that in variable of price perception and design have strong enough relation to purchasing decision, beside that independent variable have contribution equal to 54,2 % to dependent variable and rest 45,8% influenced by other variable. To test the validity and reliability test of this research declared valid and reliable. In the simultaneous test result ( F test) has a value of 55,047 with a significance level of 0.00 and for all partial test results (t test) obtained with a significance of < 0,05.Â Keywords :price perception, design, and purchasing decision